2022
DOI: 10.2474/trol.17.207
|View full text |Cite
|
Sign up to set email alerts
|

Modified Reynolds Equations for Thin Film Lubrication with Saturated High-Viscosity Surface Layer and Lubrication Analysis of Tapered Pad Bearing

Abstract: This paper presents a modified Reynolds equation for analyzing thin film lubrication with a saturated high-viscosity surface layer on a solid surface. The saturated high-viscosity characteristics of engine oil blended with additives of metallic detergents and friction modifiers were expressed using new viscosity functions with various orders termed "viscosity model 2," which is different from the previous model, termed "viscosity model 1." The viscosity function was then incorporated on the moving surface, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(18 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…The quantities Z c and z c are referenced film thicknesses close to the saturated viscosity film thickness when the viscosity at z = Z c and z c becomes (r 0 +1)/2 = ~r0 /2. Previous studies [16,18] demonstrated that the load capacity in the one-side model using Z c = 2z c was similar to that in the two-side model. The total saturated viscosity thickness of the effective viscosity measured by resonance shear force measurement system could correspond to Z c in Eq.…”
Section: Characteristics Of Micro-tapered Pad Bearing Lubricated By E...mentioning
confidence: 73%
See 4 more Smart Citations
“…The quantities Z c and z c are referenced film thicknesses close to the saturated viscosity film thickness when the viscosity at z = Z c and z c becomes (r 0 +1)/2 = ~r0 /2. Previous studies [16,18] demonstrated that the load capacity in the one-side model using Z c = 2z c was similar to that in the two-side model. The total saturated viscosity thickness of the effective viscosity measured by resonance shear force measurement system could correspond to Z c in Eq.…”
Section: Characteristics Of Micro-tapered Pad Bearing Lubricated By E...mentioning
confidence: 73%
“…3.1 Viscosity function when the effective viscosity is saturated below a large film thickness A previous study [17,18] indicated that a high-viscosity surface layer on the moving surface could simulate the effective viscosity characteristics of engine oil comprising metallic detergent additive, which were measured by Shibasaki et al [11] and Tamura et al [12]. This high-viscosity surface layer for the one-side model is expressed by Eq.…”
Section: Characteristics Of Micro-tapered Pad Bearing Lubricated By E...mentioning
confidence: 94%
See 3 more Smart Citations